Paraoxonase-1 L/m 55 gene polymorphism in the cases of idiopathic thrombocytopenic purpura - Cakici, O.; Akarsu, S.; Erol, D.; Ustundag, B.; Yuce, H. (Elsevier Science Inc, 2009)
[Abstract Not Available]